Action Potential Clamp and Pharmacology of the Variant 1 Short QT Syndrome T618I hERG K(+) Channel - El Harchi, Aziza (Public Library of Science, 2012)
BACKGROUND: The familial Short QT Syndrome (SQTS) is associated with an increased risk of cardiac arrhythmia and sudden death. Gain-of-function mutations in the hERG K(+) channel protein have been linked to variant 1 of the SQTS. A hERG channel pore (T618I) mutation has recently been identified in families with heritable SQTS. This study aimed to determine effects of the T618I-hERG mutation on (i) hERG current (I(hERG)) elicited by ventricular action potentials; (ii) the sensitivity of I(hERG) to inhibition by four clinically used antiarrhythmic drugs. METHODS: Electrophysiological recordings of I(hERG) were made at 37°C from HEK 293 cells expressing wild-type (WT) or T618I hERG. Whole-cell patch clamp recording was performed using both conventional voltage clamp and ventricular action potential (AP) clamp methods. RESULTS: Under conventional voltage-clamp, WT I(hERG) peaked at 0-+10 mV, whilst for T618I I(hERG) maximal current was right-ward shifted to ∼ +40 mV. Voltage-dependent activation and inactivation of T618I I(hERG) were positively shifted (respectively by +15 and ∼ +25 mV) compared to WT I(hERG). The I(hERG) ‘window’ was increased for T618I compared to WT hERG. Under ventricular AP clamp, maximal repolarising WT I(hERG) occurred at ∼ -30 mV, whilst for T618I hERG peak I(hERG) occurred earlier during AP repolarisation, at ∼ +5 mV. Under conventional voltage clamp, half-maximal inhibitory concentrations (IC(50)) for inhibition of I(hERG) tails by quinidine, disopyramide, D-sotalol and flecainide for T618I hERG ranged between 1.4 and 3.2 fold that for WT hERG. Under action potential voltage clamp, T618I IC(50)s ranged from 1.2 to 2.0 fold the corresponding IC(50) values for WT hERG. CONCLUSIONS: The T618I mutation produces a more modest effect on repolarising I(hERG) than reported previously for the N588K-hERG variant 1 SQTS mutation. All drugs studied here appear substantially to retain their ability to inhibit I(hERG) in the setting of the SQTS-linked T618I mutation.